ANALISIS KUALITAS BUTIR SOAL UJIAN AKHIR SEMESTER GASAL MATA PELAJARAN PKSM KELAS XI TEKNIK SEPEDA MOTOR - Wulan Chikita (Jurnal Pendidikan Vokasi Otomotif, 2019)
This research was conducted with the aim to determine the quality of items about odd Semester Final Exam Subjects of Electrical Maintenance of Class XI Motorcycle Engineering at SMK Negeri 1 Bumiratu Nuban Academic Year 2018/2019. The research method used is descriptive method with a quantitative approach. The data collection technique uses the documentation method, to obtain test questions and answer keys as well as answers to all students who take the exam. The population of the study was grade XI Motorcycle Engineering SMK Negeri 1 Bumiratu Nuban 2018/2019. The results in terms of the question validity aspects as much as 57% including valid categories and 43% invalid. In terms of reliability, the reliability coefficient is 0.79 which means it has a high coefficient. Then in terms of the level of difficulty as much as 5% including the easy category, 53% including the medium category, 37% including the difficult category and 5% including the very difficult category. In terms of distinguishing factors, there were 5% of questions including excellent categories, 43% including good categories, 20% including sufficient categories, 22% including bad categories and 10% including categories that had to be discarded. From the aspect of deceptive effectiveness, there are only 7.5% of questions for which all the deceivers function effectively.